Current standards for measuring spinal range of motion for impairment - Cupon, Leanne N. (Elsevier, 2003)
Measurement of spinal range of motion (ROM) along with strength, endurance, coordination, and sensation are among the essential determinants of musculoskeletal function. These measurements are important to the chiropractic physician concentrating in the fields of impairment rating, disability evaluation and independent medical examination (forensic examiner). An important initial step toward standardizing measurement of joint motion has been undertaken by the American Medical Association with their publication The Practical Guide to Range of Motion Assessment. Their publication is an attempt to provide a detailed and illustrated description of a standardized approach to ROM measurement and recording. The College on Forensic Sciences (CFS) is spear- heading an effort to encourage and provide detailed instruction on measuring range of motion according to this companion book to the AMA Guides. This attempt at providing a systematic format should enable chiropractic (forensic) evaluators to obtain more reliable range of motion measurements/data by using the same standardized protocols, reference tables, and reporting methods.